Grouting Mechanism in Water-Bearing Fractured Rock Based on Two-Phase Flow - Bo Ren; Wenqiang Mu; Bingyou Jiang; Guofeng Yu; Lianchong Li; Tingshuang Wei; Yunchun Han; Diancai Xiao (Geofluids)
Grouting is always used in mine water plugging, reinforcement, and other disaster prevention projects. The diffusion mechanism of slurry in fractured rock is affected by geological environment and slurry performance, which should be revealed and characterized better. Based on the two-phase flow diffusion theory, a slurry diffusion model considering flowing water condition was established for a blocking area of a fracture zone in one case from China. The feasibility of two-phase flow model in grouting diffusion calculation was analyzed. The diffusion model in dynamic water environment was studied, and the diffusion range varying with time in the grouting area of Zhangji Coal Mine was explored. The optimization method of multi grouting holes was put forward, and the influence of water flowing was discussed. The results show that the slurry diffusion calculated by the two-phase flow model was feasible and consistent with the experimental study. The dynamic water can change the conventional circular diffusion state of slurry, but its pattern was oval and leaf type. There were different penetration distances in directions, and typical grouting voids were made on the side and upstream. When the single-hole grouting was carried out, the predetermined value can be achieved in the height range, but it was only about 15 m on the side because of the water flowing, which cannot meet the requirements. The optimization scheme of grouting was put forward, which adopted multiple grouting holes in the long side, and grouting in different directions and periods to avoid the possible problems of multihole intersection. The rationality and effectiveness of the proposed optimization method were verified through the calculation of water yield and analysis of cement composition from the drilling core in the grouted zone. In the grouting process, the water flowing has double effects, which has a significant role in promoting and scouring along the flow direction, but there is a significant weakness in the side diffusion. It is very important to realize the rational use of the dynamic water through the optimization scheme. This study is an important basic work of grouting mechanism, and it is expected to promote the development of grouting technology and application of two-phase fluid-solid coupling theory.